THINK PAIR SHARE (TPS) TERINTEGRASI SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR IPA DI SMP - Ajhar Ajhar; Ade Haerullah; Bahtiar Bahtiar (Universitas Khairun, 2020)
Various efforts are made to improve education quality in schools become a priority. One of the efforts that can be taken is to improve the quality of the learning process. Improving the quality of the learning process can be done by increasing the potential of the teacher as one of the elements in the learning process. The purpose of this study was to obtain student learning outcomes by implementing cooperative learning model of the type of think pair share (TPS) integrated with additives and addictive substances in food and drinks at a State Junior High School 1West Halmahera. This research is a quasi-experimental design, consisting of two experimental classes with one group pretest-posttest research design. The results showed that the think Pair share (TPS) learning model integrated scientific was able to improve student learning outcomes in additives and addictive substances in food and drinks. The pieces of evidence can be seen by the average increase in student learning outcomes before after treatment 40.84 to 73.06. Thus it can be concluded that the Think Pair Share learning model integrated science has the potential to improve student cognitive learning outcomes.